Estudio comparativo de clinkers producidos con diferentes reemplazos de combustibles residuales - Trezza, Mónica Adriana (2003)
In the last decades the cement industry has used, as a partial substitute for traditional fuel, different industrial wastes in order to profit their residuals energy. In the present work the physicochemical characteristics of clinker, obtained using trade marked alternative fuel for clinker kiln, were evaluated. X-ray diffraction (XRD), Blaine specific surface, pyrometric cone equivalent (PCE), differential thermal analysis-thermal gravimetry simultaneous (DTA-TG), differential calorimetry, porosimetry and mechanical strength were used as the main evaluation techniques of the characteristic of clinker and their behaviors in the early hydration. The additions of the wastes, within the percentages and under the conditions of this test, does no significantly alter the clinker properties but generates a greater crystallinity of the principal clinker phases.